ESG Disclosure and Capital Structure in Explaining the Value of Renewable Energy-Oriented Energy Companies - Alfina Damayanti; Rousilita Suhendah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) disclosure and capital structure on firm value in renewable energy-oriented companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Secondary data were obtained from financial, annual, and sustainability reports. Using purposive sampling, 34 observations from 7 companies were analyzed through panel data regression with EViews 12. The results show that ESG disclosure has a negative and significant effect on firm value, while capital structure has no significant effect. This study contributes to the ESG literature in Indonesia’s renewable energy sector and underscores the importance of improving ESG implementation and disclosure transparency to enhance investor confidence and support sustainable firm value